Desain Antarmuka Pengguna Aplikasi Pemesanan Menu Cafe Berbasis User-Centered Design - iza Netrysa; Suryo Widiantoro (Fakultas Komputer - Universitas Universal, 2026)
This research addresses long customer queues and manual order-recording errors at Cafe Sudut 270 Street Coffee. To solve these issues, the study designs a menu ordering system focused on an adaptive and user-friendly interface. The design process applies the User-Centered Design (UCD) approach to match actual user needs. Initial data collection relied on in-depth interviews and direct field observations. Then, a high-fidelity prototype was built using Figma. Two methods evaluated the success of the system. First, customers completed the System Usability Scale (SUS) questionnaire, which yielded an average score of 76.9 in the